2005
DOI: 10.1161/01.atv.0000183607.50230.9f
|View full text |Cite
|
Sign up to set email alerts
|

Rho/Rho-Kinase Pathway Contributes to C-Reactive Protein–Induced Plasminogen Activator Inhibitor-1 Expression in Endothelial Cells

Abstract: Objective-Rho/Rho-kinase pathway plays pivotal roles in cardiovascular diseases including arteriosclerosis and hypertension. Recently it has become evident that C-reactive protein (CRP), a powerful marker for cardiovascular events, has direct proatherothrombotic effects on vascular cells. However, its molecular mechanism has not been fully investigated. We examined the involvement of Rho/Rho-kinase signaling in CRP-induced plasminogen activator inhibitor-1 (PAI-1) expression in bovine aortic endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…Our experimental data showed a correlation between an anti-inflammatory effect measured as the reduction in hsCRP and ROCK inhibition (p<0.05) in the rosuvastatin 40 mg group. This result supports the hypothesis that the Rho/Rho-kinase pathway may be involved in CRP-induced atherothrombogenesis (32). ROCK inhibition mediates the anti-inflammatory effects of statins, and the clinical benefit is observed in patients with elevated CRP levels treated with intensive statin therapy (33).…”
Section: Discussionsupporting
confidence: 80%
“…Our experimental data showed a correlation between an anti-inflammatory effect measured as the reduction in hsCRP and ROCK inhibition (p<0.05) in the rosuvastatin 40 mg group. This result supports the hypothesis that the Rho/Rho-kinase pathway may be involved in CRP-induced atherothrombogenesis (32). ROCK inhibition mediates the anti-inflammatory effects of statins, and the clinical benefit is observed in patients with elevated CRP levels treated with intensive statin therapy (33).…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of endogenous sphingoid bases, sphingoid base-1-phosphates, and ceramide kinase (MAPK), protein kinase C (PKC), and Rho kinase (7)(8)(9)(10). Results from in vitro studies have shown that insulin and isolated lipoproteins, especially tri glyceride-rich lipoproteins, stimulate PAI-1 production by cultured endothelial cells and hepatocytes ( 11,12 ).…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…RhoA activation was assessed using a precipitation assay for RhoA-GTP in the membrane fraction, according to the manufacturer's instructions (Upstate Biotechnology, Lake Placid, NY). RhoA activation was expressed as a percentage of WT control RhoA activation [19].…”
Section: Rhoa Activation Assaymentioning
confidence: 99%